Population‐based study shows that resuscitating apparently stillborn extremely preterm babies is associated with poor outcomes. (14th July 2016) - Haines, Morgan; Wright, Ian M.; Bajuk, Barbara; Abdel‐Latif, Mohamed E.; Hilder, Lisa; Challis, Daniel; Guaran, Robert; Oei, Ju Lee
Abstract: Aim: This population‐based study determined the delivery room management and outcomes of extremely preterm infants born with Apgar scores of 0. Methods: We linked birth, neonatal intensive care unit (NICU) and death records for babies who were born between 22 + 0 and 27 + 6 weeks of gestation with a one‐minute Apgar score of 0, in New South Wales, Australia, between 1998 and 2011. Results: We classified 2173/2262 (96%) of infants with a one‐minute Apgar score of 0 as stillborn. Resuscitation was provided for 48/89 (54%) live births and 40/2173 (2%) stillbirths. Cardiac massage was given to 44 infants, including three 22‐week stillborn babies. Of the 13 live births admitted to an NICU, 11 survived to hospital discharge. Most (98%) of the 2212 deaths occurred on the first day of life. One baby who was classified as stillborn lived for 51 days. Resuscitation increased the mean (95% confidence interval) duration of survival from 1 (0–2) to 45 (0–104) hours (p < 0.001). No infant with a five‐minute Apgar score of 0 survived. Conclusion: Clinicians resuscitated extremely preterm infants without a detectable heartbeat, even at 22 weeks of gestation. No infant survived without resuscitation or if their heartbeat was not regained by five minutes.